2004
DOI: 10.1002/bsl.572
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits in adolescent offenders: an evaluation of criminal history, clinical, and psychosocial correlates

Abstract: Although a large body of research has established the relevance of psychopathy to adult offenders, its relevance to adolescent offenders is far less clear. The current study evaluated the clinical, psychosocial and criminal correlates of psychopathic traits in a sample of 226 male and female incarcerated adolescent offenders. According to an 18-item version of the Psychopathy Checklist-Youth Version (PCL-YV; Forth, Kosson, & Hare, 2003), only 9.4% exhibited a high level of psychopathic traits (PCL-YV>/=25). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
1
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 60 publications
20
124
1
17
Order By: Relevance
“…Several studies have since documented a link between psychopathic traits and childhood trauma. For example, in their seminal longitudinal study of 652 young adults, Weiler and Widom (1996) found that individuals with a legally documented history of childhood abuse/neglect were significantly more likely than a matched control sample of 489 individuals without a documented history of maltreatment to develop psychopathic traits and violent behavior approximately 20 years later (see also Bernstein, Stein, & Handelsman, 1998;Campbell, Porter, & Santor, 2004;Krischer & Sevecke, 2008). Similarly, developmental research indicates that trauma exposure (abuse, neglect) during toddlerhood is associated with early affective deficits consistent with CU traits, namely a lack of empathy and concern for others (Main & George, 1985).…”
Section: Violence Exposure Mediates the Relation Between Callous-unemmentioning
confidence: 99%
“…Several studies have since documented a link between psychopathic traits and childhood trauma. For example, in their seminal longitudinal study of 652 young adults, Weiler and Widom (1996) found that individuals with a legally documented history of childhood abuse/neglect were significantly more likely than a matched control sample of 489 individuals without a documented history of maltreatment to develop psychopathic traits and violent behavior approximately 20 years later (see also Bernstein, Stein, & Handelsman, 1998;Campbell, Porter, & Santor, 2004;Krischer & Sevecke, 2008). Similarly, developmental research indicates that trauma exposure (abuse, neglect) during toddlerhood is associated with early affective deficits consistent with CU traits, namely a lack of empathy and concern for others (Main & George, 1985).…”
Section: Violence Exposure Mediates the Relation Between Callous-unemmentioning
confidence: 99%
“…Indeed, researchers have cited the benefits of understanding the etiology of the disorder (Forth & Burke, 1998;Lynam, 1996), targeting interventions (Forth & Mailloux, 2000;Frick, Bodin, & Barry, 2000) and increasing case management efficiency (Campbell, Porter, & Santor, 2004;Corrado, Vincent, Hart, & Cohen, 2004) as a justification for extending the PCL-R to adolescents. But we should be careful that our desire to 'nip psychopathy in the bud' does not push our practice further than justified by empirical research.…”
Section: Nipping Psychopathy In the Bud: Clinical And Policy Implicatmentioning
confidence: 99%
“…Results suggested that CU traits were associated with lower emotional distress and a specific social information-processing pattern. Campbell, Porter, and Santor (2004) evaluated the clinical, psychosocial and criminal correlates of psychopathic traits in a sample of 226 male and female incarcerated adolescent offenders. No significant differences were found between males and females regarding the PCL: YV scores.…”
Section: Introductionmentioning
confidence: 99%